Absence of penicillin-binding protein 4 from an apparently normal strain of Bacillus subtilis. - Buchanan, C E (1987)
The phenotype of a Bacillus subtilis 168 strain with no detectable penicillin-binding protein 4 was examined. Despite the fact that penicillin-binding protein 4 is one of the most penicillin-sensitive proteins in the species, its apparent loss had no obvious effect on the organism or its susceptibility to various beta-lactam antibiotics.